Nimmer on Copyright : Volume 11 Reference Materials Appendices 58-End Table of References Table of Cases Index - Melville B Nimmer; David Nimmer (Haryana, India LexisNexis, 2010)
School of Law, Governance and Public Policy
MIR No:317
Keywords: Law